Clinical characteristics of palmoplantar discoid lupus erythematosus: A multicenter retrospective review of 43 patients - Katharina Shaw; Catherina Pan; Stephanie Sanchez‐Melendez; Dustin Taylor; Neda Shahriari; Lyn Duncan; Avery LaChance; Ruth Ann Vleugels (Wiley, 2023)
Abstract Background Palmoplantar discoid lupus erythematosus (ppDLE) is a rare manifestation of chronic cutaneous lupus erythematosus that can result in painful, hyperkeratotic, and/or erosive lesions on the palms and soles. Despite this penchant to cause significant morbidity, the natural history of ppDLE and its response to conventional treatment approaches remain poorly understood. Objectives To characterize the initial presentation, treatment response, and association with systemic lupus erythematosus (SLE) of ppDLE. Methods We performed an International Classification of Diseases (ICD‐9 and ICD‐10) code and natural‐language query for medical records from Brigham and Women's Hospital and Massachusetts General Hospital to identify all cases of ppDLE based on biopsy and/or expert opinion from January 2000 through October 2022. Demographics, clinical features, and treatment data were analysed. Results Forty‐three patients (median age, 29.5 years [range, 8−70 years]; 36 female [83.7%]) with ppDLE were identified. Mean time from initial clinical presentation of ppDLE symptoms to diagnosis was 14.5 months (n = 34). Of the 43 patients, 74.4% developed coexistent SLE. A mean of 5.9 (standard deviation, 2.7) lines of therapy were required to achieve control of ppDLE, with the majority of patients requiring the initiation of at least two concomitant systemic medications. Conclusions Herein, we present the largest cohort of patients with ppDLE in the literature to date. Despite a high incidence of coexistent SLE, patients experienced lengthy diagnostic delays. Even with appropriate diagnosis, an overwhelming trend towards treatment‐refractory disease was observed.